EPCO-02. GERMLINE SINGLE NUCLEOTIDE POLYMORPHISM rs55705857 AT 8q24 INTERACTS WITH SOMATIC IDH1 MUTATION TO ENHANCE HUMAN GLIOMA FORMATION. (12th November 2021) - Drucker, Kristen; Yanchus, Connor; Kollmeyer, Thomas; Ali, Asma; Paul, Decker; Kosel, Matthew; Panda, Arijit; Caron, Alissa; Giannini, Caterina; Burns, Terence; Abyzov, Alexej; Wang, Liguo; et al.
Abstract: BACKGROUND: Determination of the causation of germline single nucleotide polymorphisms (SNPs) located in non-coding regions of the genome is challenging. The genomic region of 8q24 has been identified as important in many kinds of cancer, linked to a topologically associated domain (TAD) encompassing MYC; this TAD contains a GWAS SNP (rs55705857) associated with IDH-mutant glioma. METHODS: Germline genotyping data from 622 IDH-mutant glioma and 668 controls were used to fine map the rs55705857 locus by detailed haplotype analysis. Chromatin immunoprecipitation sequencing (ChIP-seq) of histone markers H3K4me 1, H3K4me 3, H3K27ac and H3K36me 3 was performed on normal brain samples (n=8) and human glioma samples (n=11 IDH-wt and 52 IDH-mut). RNAseq from 9 normal and 83 brain tumors (n=26 IDH-wt and 55 IDH-mut) were used to assess differential gene expression. RESULTS: Fine-mapping identified rs55705857 SNP as the most likely causative allele (OR=8.69; p<0.001) within 8q24 for the development of IDH-mutant glioma. At rs55705857, both H3K27ac and H3K4me 1 in IDH-mutant vs IDH-wt tumors were increased 3.05- and 1.58-fold, respectively (DiffBind; p=5.81×10 -7 and p=2.31×10 -3 ). ChromHMM analysis of the marks indicated that promoter and enhancer functions were significantly increased, and the activity broadened at rs55705857 in IDH-mut gliomas compared to IDH-wt tumors and normal brain samples. This enhancement correlated with significant increased MYC expression in IDH-mut gliomas (p=3.1×10 -13 ), as well as alterations of Myc signaling targets. Publicly available ATACseq, ChIPseq and long-range DNA interaction data demonstrated that the rs55705857 locus is open and interacts with the MYC promoter. CONCLUSIONS: Fine-mapping of the 8q24 locus provided strong evidence that rs55705857 is the causative 8q24 locus associated with IDH-mut glioma. Functional experiments suggest that IDH mutation facilitates rs55705857 interaction with MYC to alter downstream MYC targets.